Capture-based hatchery of black tiger shrimp (Penaeus monodon) in Vietnam: an analysis of resource utilisation and challenges - Vo, Son Nam; Cu, Thuy Thi Le; Chau, Tao Tai; Nguyen, Long Thanh; Tang, Tinh Thien; Au, Hoa Van; Tran, Khoa Nguyen Duy; Nguyen, Quynh Do; Ho, Viet Van; Trinh, Tu Quang; Phan, Tran Bao; Norden, Wendy; et al. (Frontiers in Marine Science, 2024)
Introduction: This study aimed to evaluate the status, resource use, and challenges of the capturebased hatchery of black tiger shrimp (Penaeus monodon) (BTS).Methods: Data was obtained through the investigation of 15 broodstock fishing boats and 60 capturebased BTS broodstock hatcheries. Resource use index (RUI) of the capture-based BTS hatchery, calculated from 1,000 female brooders to produce 15-day-old post-larvae (PL15) (production efficiency of PL15, or PE-PL15), was analysed.The results indicated that the fishing boats captured an average of 5,900 brooders.boat -1 .year - 1 , 20,856 kg of by catch.boat -1 .year -1 , and the PE-PL15 production of 937 million for 1,000 female brooders. In the hatchery stage, the use of larger body weight female brooders had benefits in terms of higher survival rate and better efficiency of labour use, Artemia cyst, and probiotic products, but it reduced the efficiency use of chemicals, pellets, and total tank volume of the hatchery. .Discussion: There is increasing use of domesticated brooder sources, but wild-caught brooders still play an important role in producing low-cost PL15 for traditional shrimp farming systems, accounting for most farmed BTS production. Therefore, the certification of good practices should be implemented to capture-based BTS hatcheries for the reasonable use of this brooder resource to sustain BTS farming in Vietnam.